The Effect Of Digital Marketing On Consumer Purchase Intention In Micro, Small And Medium Enterprises In Yhe Food Sector In Makassar City - Hasan Basri; Imam Mujahidin Fahmid (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze the effect of digital marketing on consumer purchase intention in micro, small, and medium enterprises (MSMEs) in the food sector. The research was conducted on food sector MSMEs in Makassar City, South Sulawesi Province. The sample in this study consisted of 100 respondents. The sampling technique used was incidental sampling. The type of data used in this study was quantitative data. Data collection was conducted through observation and interviews with respondents, followed by the distribution of questionnaires. The collected data were then analyzed using simple linear regression analysis. The results of the study indicate that there is a significant and positive effect of digital marketing on consumer purchase intention in food sector MSMEs in Makassar City. This means that the better the implementation of digital marketing by food sector MSME actors, the higher the consumer purchase intention will be. Conversely, if the implementation of digital marketing is poor, consumer purchase intention will decrease.